Recombinant proteins production in Escherichia coli BL21 for vaccine applications: a cost estimation of potential industrial-scale production scenarios - Akmayan, Ilkgul; Ozturk, Abdullah Bilal; Ozbek, Tulin (TAYLOR & FRANCIS INC, 2024)
Recent SARS-CoV-2 pandemic elevated research interest in microorganism-related diseases, and protective health application importance such as vaccination and immune promoter agents emerged. Among the production methods for proteins, recombinant technology is an efficient alternative and frequently preferred method. However, since the production and purification processes vary due to the protein nature, the effect of these differences on the cost remains ambiguous. In this study, brucellosis and its two important vaccine candidate proteins (rOmp25 and rEipB) with different properties were selected as models, and industrial-scale production processes were compared with the SuperPro Designer (R) for estimating the unit production cost. Simulation study showed raw material cost by roughly 60% was one of the barriers to lower-cost production and 52.5 and 559.8 $/g were estimated for rEipB and rOmp25, respectively.
Keywords: Recombinant protein; Prokaryotic expression system; Vaccine; Process simulation; Cost estimation; OUTER-MEMBRANE PROTEIN; BRUCELLA-ABORTUS; TECHNOECONOMIC ANALYSIS; WASTE VALORISATION; PURIFICATION; EXPRESSION; FOOD; FERMENTATION; OPTIMIZATION; MELITENSIS; Biochemistry & Molecular Biology; Biotechnology & Applied Microbiology